Endogenous Bok is stable at the endoplasmic reticulum membrane and does not mediate proteasome inhibitor-induced apoptosis - Bonzerato, Caden G.; Keller, Katherine R.; Schulman, Jacqualyn J.; Gao, Xiaokong; Szczesniak, Laura M.; Wojcikiewicz, Richard J. H. (Frontiers in Cell and Developmental Biology, 2022)
Controversy surrounds the cellular role of the Bcl-2 family protein Bok. On one hand, it has been shown that all endogenous Bok is bound to inositol 1,4,5-trisphosphate receptors (IP3Rs), while other data suggest that Bok can act as a pro-apoptotic mitochondrial outer membrane permeabilization mediator, apparently kept at very low and non-apoptotic levels by efficient proteasome-mediated degradation. Here we show that (i) endogenous Bok is expressed at readily-detectable levels in key cultured cells (e.g. mouse embryonic fibroblasts and HCT116 cells) and is not constitutively degraded by the proteasome, (ii) proteasome inhibitor-induced apoptosis is not mediated by Bok, (iii) endogenous Bok expression level is critically dependent on the presence of IP3Rs, (iv) endogenous Bok is rapidly degraded by the ubiquitin-proteasome pathway in the absence of IP3Rs at the endoplasmic reticulum membrane, and (v) charged residues in the transmembrane region of Bok affect its stability, ability to interact with Mcl-1, and pro-apoptotic activity when over-expressed. Overall, these data indicate that endogenous Bok levels are not governed by proteasomal activity (except when IP3Rs are deleted) and that while endogenous Bok plays little or no role in apoptotic signaling, exogenous Bok can mediate apoptosis in a manner dependent on its transmembrane domain.